Big Five Personality Traits dan Skeptisisme Profesional Auditor - Saraswati, Putu Bernika; Latrini, Made Yenni (E-Jurnal Akuntansi, 2023)
Professional skepticism is an attitude that consistently questions and critically evaluates audit evidence. A high attitude of professional skepticism will produce a quality audit report in which the personality factor is one of the factors. Personality indicators that are declared valid are the big five personality. The aim of this study is to empirically prove the effect of the big five personality traits on the professional skepticism of auditors in the Public Accounting Firm of the Province of Bali. The research was conducted at the Bali Province Public Accountant Office by distributing questionnaires. The research sample is 55 auditors, determined by purposive sampling method. Data were analyzed using multiple linear analysis techniques. The results of the study prove that the traits of openness to experience, conscientiousness, extraversion, and agreeableness have a significant positive effect, while neuroticism has a significant negative effect on the auditor's professional skepticism. Keywords: Professional Skepticism; Big Five Personalit; Auditor’s Personality Traits; Public Accounting Firm